1998
DOI: 10.1021/ac971337v
|View full text |Cite
|
Sign up to set email alerts
|

13C Dynamic Nuclear Polarization:  an Alternative Detector for Recycled-Flow NMR Experiments

Abstract: Static NMR experiments on insensitive nuclei (e.g., (13)C) have been generally difficult because of low magnetogyric ratios and/or poor natural abundance, even at the highest magnetic fields available. One method of overcoming these sensitivity limitations is dynamic nuclear polarization (DNP), which can be utilized to enhance NMR signals relative to those obtained with static NMR detection. In this study, we report a recycled-flow DNP apparatus capable of monitoring (13)C scalar-dominated enhancements 1-2 ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 34 publications
1
23
0
Order By: Relevance
“…The SLIT approach also has the advantage of improved low to high magnetic eld transfer efficiencies allowing the transfer of radical free hyperpolarized metabolites for biological uses. 53,54 The use of immobilized radicals for DNP approaches has recently been reconsidered and utilized to generate hyperpolarized water for clinical MRI applications. [11][12][13]55,56 The efficiency of interactions between the radical and nuclei in immobilized radical ow methods can be in fact improved through better design of immobilizing methods, 11,57 as well as the optimum synthesis of new radicals.…”
Section: Introductionmentioning
confidence: 99%
“…The SLIT approach also has the advantage of improved low to high magnetic eld transfer efficiencies allowing the transfer of radical free hyperpolarized metabolites for biological uses. 53,54 The use of immobilized radicals for DNP approaches has recently been reconsidered and utilized to generate hyperpolarized water for clinical MRI applications. [11][12][13]55,56 The efficiency of interactions between the radical and nuclei in immobilized radical ow methods can be in fact improved through better design of immobilizing methods, 11,57 as well as the optimum synthesis of new radicals.…”
Section: Introductionmentioning
confidence: 99%
“…13 C enhancements for halogenated compounds were demonstrated in the late 1990's [45,46]. Han and co-workers demonstrated a continuous flow approach to polarize water in the fringe field of an MRI magnet for imaging [47].…”
Section: Low Field Overhauser Dnp and High Field Nmr Detectionmentioning
confidence: 99%
“…Therefore, and unlike in static experiments, for flow experiments the enhancement gathered at the MRI scanner is not scaled only by the ratio of magnetic fields. Dorn et al [18] showed that instead, one has take into account the different relaxation and buildup processes at different magnetic fields. Hence, correlating the enhancement in the Halbach magnet and the MRI scanner is very difficult.…”
Section: Flow Dnp At 035 Tmentioning
confidence: 99%
“…Dorn et al [16][17][18] addressed the challenge of radical immobilization already in the late 1980s and 1990s, but did not investigate biocompatible molecules. Han et al picked up the idea, improved the attainable enhancement by magnitudes introducing spin-labeled Sepharose gel and investigated water as an authentic contrast agent [12,19,20].…”
Section: Introductionmentioning
confidence: 99%